2018
DOI: 10.1016/j.sna.2018.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic motor performance influenced by lubricant properties

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…pipe-crawling robots [10] or optical instrument for endoscopic usage [12]). Improvement of the frictional condition can be achieved by utilizing the friction materials [17,25,26], modifying the surface morphology [27][28][29], or using the lubrication [30]. As typical examples, Zhao et al [25] used aramid/molybdenum-disulfide composites as the friction materials from the viewpoint that the variation in aramid's glass transition temperature could improve tribological performance of USMs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…pipe-crawling robots [10] or optical instrument for endoscopic usage [12]). Improvement of the frictional condition can be achieved by utilizing the friction materials [17,25,26], modifying the surface morphology [27][28][29], or using the lubrication [30]. As typical examples, Zhao et al [25] used aramid/molybdenum-disulfide composites as the friction materials from the viewpoint that the variation in aramid's glass transition temperature could improve tribological performance of USMs.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [27] stated that the wear mechanisms of friction materials sliding against the textured vibrator were mainly caused by the fatigue especially for small-sized friction materials; this provided the criterion to choose USMs' friction materials. Qiu et al [30] found that the lubrication with high-traction fluid is helpful to improve USMs' performance owing to the fluid's special capability to reduce friction loss. Though improvement of the frictional condition has been proven as an effective way for certain types of USMs [17], owing to the fact that the vibration characteristics are mainly determined by the vibrators' material properties [1,8], we still regard that the usage of new materials is prospective for improving USMs' performance [9].…”
Section: Introductionmentioning
confidence: 99%